2022
DOI: 10.3390/su141610111
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexities of Human Well-Being in the Context of Ecosystem Services within Coastal Ghana

Abstract: The understanding of the complexities of human well-being (HWB) within the ecosystem service (ES) context is fundamental to the development of management plans to sustain the flow of ecosystem services (ESs) for HWB. However, research on HWB in the context of ecosystem services is still underrepresented on Africa’s coast. Primary data were collected from 794 household heads in six communities within Ghana’s eastern coastal zone. A sequential logistics regression model was used to assess the effect of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…As important as psychological well-being is, however, previous studies have found that while the salaries and welfare of employees in China and India have increased rapidly over recent decades, the psychological well-being of people in these countries, as measured by national surveys, has hardly changed [3,4]. As such, a growing number of researchers have come to focus on the task of investigating the factors that may affect employee psychological well-being [1,2,[4][5][6][7]. One stream of research in recent years has argued that firms can improve employee psychological wellbeing by engaging in corporate social responsibility (CSR) [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As important as psychological well-being is, however, previous studies have found that while the salaries and welfare of employees in China and India have increased rapidly over recent decades, the psychological well-being of people in these countries, as measured by national surveys, has hardly changed [3,4]. As such, a growing number of researchers have come to focus on the task of investigating the factors that may affect employee psychological well-being [1,2,[4][5][6][7]. One stream of research in recent years has argued that firms can improve employee psychological wellbeing by engaging in corporate social responsibility (CSR) [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…To be successful, restoration needs to increase ecosystem service provision, and those services must then increase wellbeing. Since 2005, it has been understood that the ecosystem services–wellbeing relationship is not linear (Millennium Ecosystem Assessment 2005) and research has repeatedly found this relationship to be complex, variable, and understudied (Cruz‐Garcia et al 2017; Duku et al 2022; Liu et al 2022).…”
Section: Barrier: Lack Of Understanding How Ecosystem Services Increa...mentioning
confidence: 99%
“…Furthermore, the International Panel on Biodiversity and Ecosystem Services (IPBES) advertises for the inclusion of traditional and indigenous knowledge into ecosystem service assessments [60], which can be used just as well, or, even better, to set the social-ecological context of a study area. In data-scarce regions, ecosystem service assessments often depart in household surveys or participatory mapping approaches, e.g., [61,62], where our approach could be a complement to structure the information in preparation and support of a discussion process. In that case, the ecosystem services used in this study would need to be carefully revised with local stakeholders to capture the dominating uses and worldview.…”
Section: Transferability Of the Assessment Approach: Esas In Data-sca...mentioning
confidence: 99%